BEYOND RATIONALITY: THE EFFECT OF OVERCONFIDENCE, HERDING, AND LOSS AVERSION ON STOCK RETURNS AND TRADING VOLUME ON THE INDONESIAN STOCK EXCHANGE - Widnyana, I Wayan; Budiyasa, I Gede Putu Eka (Penelitian dan Pengembangan Ilmu, 2025)
This study aims to analyze the influence of psychological biases such as investor overconfidence, herding behavior, and loss aversion on stock returns and trading volume on the Indonesia Stock Exchange (IDX). The research background stems from a critique of classical financial theory, particularly the Efficient Market Hypothesis (EMH), which assumes investors are always rational. In reality, empirical phenomena in the Indonesian capital market demonstrate irrational behavior that is difficult to explain with classical theory.The research method employed a quantitative approach with secondary data from 60 financial and consumer sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. The independent variables tested included overconfidence, herding behavior, and loss aversion, while the dependent variables were stock returns and trading volume. Data analysis was performed using multiple linear regression after classical assumption testing to ensure model validity.The results showed that overconfidence had a significant positive effect on trading volume, herding behavior had a significant positive effect on stock returns, and loss aversion had a significant negative effect on stock returns. These findings confirmed all three research hypotheses and bolstered the behavioral finance literature, which suggests that investors are not always rational.The implications of this research are important for investors, issuers, and regulators. Investors need to increase their awareness of psychological biases to make more rational transactions. Issuers must understand that stock prices are influenced not only by fundamentals but also by market sentiment. Regulators need to strengthen financial literacy based on behavioral finance and increase oversight of herding behavior in the digital era.